Ensemble learning: a study on the border inspection prediction model for high-risk products adulterated with Sudan Red in Taiwan - Li-Ya Wu; Wei-Chih Cheng; King-Fu Lin; Jia-Jhen Lee; Wen-Chou Lin; Hsu-Yang Lin; Chia-Yen Lu; Chih-Kang Chiang (Food Control, 2026)

Biological safety assessment of dissolved aluminum ions in coastal seawater: acute toxicity effects on Pacific whiteleg shrimp (Litopenaeus vannamei) Post-larvae - Pei-Hsuan Wu; Yen-Kung Hsieh; Tsang-Hsieh Hung; Wei-Shan Chou; Ya-Rung Wu; Ping Chen; Jin-Li Yu; Chao-Kai Kang (Ecotoxicology, 2026)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Transfer learning enables robust prediction of cellular toxicity from environmental micro- and nanoplastics - Kunpeng Chen; Keyuan Li; Alexa Canchola; Jinyong Liu; Qing Liu; Wei-Chun Chou (Journal of Hazardous Materials, 2025)

Controlled preparation of vanadium nitride nanoparticles modified carbon foam hybrids for efficient synergetic confinement and catalytic conversion of polysulfides in Li-S batteries - Zhe Hu; Dengbang Jiang; Li Wang; Linyue Qu; Qian Su; Kaijiao Duan; Mingwu Xiang; Junming Guo; Wei Bai; Shulei Chou (Chemical Engineering Journal, 2025)

Biomass energy for a sustainable Taiwan: Technologies, policies, and future prospects - Yu-Wei Lin; Yu-Ting Liu; Li-Cheng Huang; Shing-Chou Lin; Shean-Jen Chen; YongMan Choi (Biomass and Bioenergy, 2025)

Hydrological changes in the East Asian monsoon region around 4.2 ka precisely reconstructed from multi-proxy stalagmites - Chao-Jun Chen; Yao Wu; Jun-Yun Li; Hai-Wei Zhang; Hai Cheng; Chuan-Chou Shen; You-Feng Ning; Dao-Xian Yuan; R. Lawrence Edwards; Jian Zhang; Ting-Yong Li (Quaternary Science Reviews, 2025)

PM2.5 episodes in northern Taiwan under southerly winds in late winter - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Meng-Hsuan Li; Shyh-Wei Chen; Shu-Hao Chang (Atmospheric Research, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

To be or not to be: The fate of submerged macrophyte biodiversity in the plateau lakes after restoration for the last decade - Qingxiang Han; Junyao Sun; Qingchuan Chou; Te Cao; Wei Li; Yu Cao (Journal of Environmental Management, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Polyphenol nanoparticles based on bioresponse for the delivery of anthocyanins - Zhihuan Zang; Yuan Li; Shurui Chou; Jinlong Tian; Xu Si; Yuehua Wang; Hui Tan; Ningxuan Gao; Chi Shu; Dongnan Li; Wei Chen; Yi Chen; et al. (Food Research International, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

LncRNA NR_030777 promotes mitophagy by targeting CDK1-related mitochondrial fission and ATG12 to attenuate paraquat-induced Parkinson's disease - Nengzhou Chen; Hong Hu; Jianping Tang; Fuli Zheng; Zhenkun Guo; Xinpei Lin; Michael Aschner; Wenya Shao; Guangxia Yu; Ping Cai; Wei-Chun Chou; Siying Wu; et al. (Environmental Pollution, 2024)

GNN-LSTM-based fusion model for structural dynamic responses prediction - Po-Chih Kuo; Yuan-Tung Chou; Kuang-Yao Li; Wei-Tze Chang; Yin-Nan Huang; Chuin-Shan Chen (Engineering Structures, 2024)

Identify organic contaminants of high-concern based on non-targeted toxicity testing and non-targeted LC-HRMS analysis in tap water and source water along the Yangtze River - Shaoqing Zhang; Liben Chou; Wenxuan Zhu; Wenrui Luo; Chi Zhang; Jingfan Qiu; Meishuang Li; Haoyue Tan; Jing Guo; Chang Wang; Keng Tu; Kefan Xu; et al. (Water Research, 2024)

Investigation of organic contaminants in the blubber of a blue whale (Balaenoptera musculus) first stranded on the coast of Taiwan - Jing-O. Cheng; Pei-Ling Wang; Li-Chin Chou; Chig-Wei Chang; Hao Ven Wang; Wei-Cheng Yang; Fung-Chi Ko (Environmental Science and Pollution Research, 2024)

The Rpf107 gene, a homolog of LOR, is required for the symbiotic nodulation of Robinia pseudoacacia - Yuanli Li; Yuanyuan Wu; Ziyi Yang; Rui Shi; Lu Zhang; Zhao Feng; Gehong Wei; Minxia Chou (Planta, 2024)

The synthesis and secretion of key substances in the flavonoid metabolic pathway responding to different nitrogen sources during early growth stages in Robinia pseudoacacia - Yuanli Li; Yongrui Shen; Rui Shi; Ziyi Yang; Yifu Chen; Wen Luo; Gehong Wei; Minxia Chou (Plant and Soil, 2024)

Assessing the Relationship between Sea Turtle Strandings and Anthropogenic Impacts in Taiwan - Wei-Rung Chou; Po-Yu Wu; Tsung-Hsien Li (Journal of Marine Science and Engineering, 2023)
Data acquired from stranded sea turtles can provide awareness of human activities that adversely affect sea turtle populations. We assessed strandings of five sea turtle species between 2017 and 2021. This study utilizes principal component analysis (PCA) and structural equation modeling (SEM) to reveal potential causes of sea turtle strandings linked to anthropogenic effects in Taiwan. Although our study did not observe a statistically significant impact of offshore wind turbines on sea turtle strandings, it did find evidence of a significant direct effect of coral colony density, heavy metals, and fishing disturbance on such strandings. For the conservation of endangered sea turtles, we recommend the incorporation of PCA and SEM in further contexts for validating anthropogenic impact assessments.

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Combining hybrid nanoflowers with hybridization chain reaction for highly sensitive detection of SARS-CoV-2 nucleocapsid protein - Wen Yin; Ji Hu; Fang Chen; Li Zhu; Yingxin Ma; Nuo Wang; Hongping Wei; Hang Yang; Shan-Ho Chou; Jin He (Analytica Chimica Acta, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Buffering capacity of submerged macrophytes against nutrient pulses increase with its coverage in shallow lakes - Chaochao Lv; Yuqing Tian; Liangliang Huang; Hang Shan; Qingchuan Chou; Wei Zhang; Haojie Su; Kuanyi Li; Xiaolin Zhang; Leyi Ni; Te Cao; Erik Jeppesen (Chemosphere, 2023)

Positive response of host root-associated bacterial community and soil nutrients to inhibitory parasitism of dodder - Wen Luo; Yuanli Li; Yidan Jia; Yifu Chen; Da Li; Ruiping Luo; Gehong Wei; Minxia Chou; Weimin Chen (Plant and Soil, 2023)

Identification of Rhodosorus marinus isolated in Taiwan and study on its optimum culture conditions - Wei Qing Chloe Lung; Jane Wungen-Sani; Chi-Cheng Huang; Chien-Li Chen; Hung-Chih Lai; Yeh-Fang Hu; Po-Tsang Lee; Fan-Hua Nan; Han-Yang Yeh; Meng-Chou Lee (Journal of Applied Phycology, 2023)

Environment and time drive the links between the species richness and ecosystem multifunctionality from multitrophic freshwater mesocosms - Zhiyan Xu; Hui Yang; Hongzhi Mao; Qiutong Peng; Shiwen Yang; Qingchuan Chou; Yujing Yang; Zhongqiang Li; Lifei Wei (Frontiers in Marine Science, 2023)
Understanding the link between biodiversity and ecosystem functioning is imperative for ecosystem-based management. The role of multitrophic diversity in sustaining multifunctionality remains unclear, especially in highly diverse aquatic ecosystems. We performed a species-addition experiment consisting of one, two, three, and five species in simulated multitrophic ecosystems to evaluate biodiversity and ecosystem functioning relationships within and across trophic levels. Our results showed that there are positive species richness–productivity relationships within and across trophic levels. We found significant negative correlations between species richness and the cumulative variation of total phosphorus, and between species richness and ecosystem multifunctionality across trophic levels. Also, we found that the relationships between ecosystem multifunctionality and species richness within and across the trophic levels are mediated by a combination of environmental factors, including water temperature, dissolved oxygen, pH, irradiance, and time, rather than by species richness. Our results imply that species richness–ecosystem functioning relationships vary for different ecological functions; the individual ecosystem functions selected and the way multifunctionality calculated are critical when examining links between biodiversity and ecosystem multifunctionality. Our study highlights that multitrophic richness, such as for consumers, is crucial for driving ecosystem multifunctionality. Furthermore, our study implies that management practices for restoring the diversity of aquatic macrophytes in wetlands should consider not only macrophyte richness but also different functional groups and life-forms.

Publisher Correction to: Compression Sleeve Changes Corticomuscular Connectivity and Sensorimotor Function - Wen‑Wen Yang; Li‑Ling Hope Pan; Chen‑Sheng Chen; Shun‑Hwa Wei; Chiang Liu; Li‑Wei Chou (Journal of Medical and Biological Engineering, 2022)

The Fvclp1 gene regulates mycelial growth and fruiting body development in edible mushroom Flammulina velutipes - Xiaomeng Lyu; Siyuan Jiang; Li Wang; Tiansheng Chou; Qingji Wang; Li Meng; Irum Mukhtar; Baogui Xie; Wei Wang (Archives of Microbiology, 2021)

Identification of Neuronal Polarity by Node-Based Machine Learning - Chen-Zhi Su; Kuan-Ting Chou; Hsuan-Pei Huang; Chiau-Jou Li; Ching-Che Charng; Chung-Chuan Lo; Daw-Wei Wang (Neuroinformatics, 2021)
Identifying the direction of signal flows in neural networks is important for understanding the intricate information dynamics of a living brain. Using a dataset of 213 projection neurons distributed in more than 15 neuropils of a Drosophila brain, we develop a powerful machine learning algorithm: node-based polarity identifier of neurons (NPIN). The proposed model is trained only by information specific to nodes, the branch points on the skeleton, and includes both Soma Features (which contain spatial information from a given node to a soma) and Local Features (which contain morphological information of a given node). After including the spatial correlations between nodal polarities, our NPIN provided extremely high accuracy (>96.0%) for the classification of neuronal polarity, even for complex neurons with more than two dendrite/axon clusters. Finally, we further apply NPIN to classify the neuronal polarity of neurons in other species (Blowfly and Moth), which have much less neuronal data available. Our results demonstrate the potential of NPIN as a powerful tool to identify the neuronal polarity of insects and to map out the signal flows in the brain’s neural networks if more training data become available in the future.

Analyzing 13 Years of Cetacean Strandings: Multiple Stressors to Cetaceans in Taiwanese Waters and Their Implications for Conservation and Future Research - Wen-Ta Li; Lien-Siang Chou; Hue-Ying Chiou; I-Hua Chen; Wei-Cheng Yang (Frontiers in Marine Science, 2021)
This study summarizes the postmortem investigations of 73 cetaceans stranded on the coast of Taiwan between 2001 and 2013, including 51 Delphinidae, 17 Kogiidae, 3 Ziphiidae, 1 Physeteridae, and 1 Balaenopteridae. Of these, eight (11%) were categorized into direct human-related strandings, including fisheries interaction (bycatch), vessel collision and other anthropogenic-related pathology. Gastrointestinal foreign bodies were found in eight individuals (11%). Most of the bacteria isolated from stranded dolphins were zoonotic pathogens including extended-spectrum β-lactamases Escherichia coli , which indicates waste pollution from land. Severe parasite infestation was found in 36 of the cases (49%), which suggests that the immune function could be compromised. Thirty-eight cases (52%) were diagnosed with myocardial patchy fibrosis or dilated cardiomyopathy. The evidence shown here indicates that cetaceans around Taiwanese waters may suffer from multiple stressors. This study provides baseline data for the health assessment of cetacean populations in Taiwan, which may ultimately provide recommendations for future cetacean conservation and research throughout the western Pacific.

Multifunctionality and microbial communities in agricultural soils regulate the dynamics of a soil-borne pathogen - Yanqing Guo; Hui Luo; Li Wang; Mingying Xu; Yongshan Wan; Minxia Chou; Peng Shi; Gehong Wei (Plant and Soil, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Compression Sleeve Changes Corticomuscular Connectivity and Sensorimotor Function - Wen-Wen Yang; Li-Ling Hope Pan; Chen-Sheng Chen; Shun-Hwa Wei; Chiang Liu; Li-Wei Chou (Journal of Medical and Biological Engineering, 2021)

Clinical Efficacy of a New Robot-assisted Gait Training System for Acute Stroke Patients - Andy Chien; Fei-Chun Chang; Nai-Hsin Meng; Pei-Yu Yang; Ching Huang; Li-Wei Chou (Journal of Medical and Biological Engineering, 2021)
Purpose Robot-assisted gait rehabilitation has been proposed as a plausible supplementary rehabilitation strategy in stroke rehabilitation in the last decade. However, its exact benefit over traditional rehabilitation remain sparse and unclear. It is therefore the purpose of the current study to comparatively investigate the clinical benefits of the additional robot-assisted training in acute stroke patients compared to standard hospital rehabilitation alone. Methods Ninety acute stroke patients (< 3 month) were recruited. All participants received the standard hospital neurorehabilitation comprises 45–60 min sessions daily for 3 weeks. Sixty patients also received an additional 30 min of robot-assisted gait training with the HIWIN MRG-P100 gait training system after each of the standard neurorehabilitation session. Outcome measures included: 1. Berg Balance Scale (BBS); 2. Brunnstrom Stage; 3. Pittsburgh Sleep Quality Index and 4. Taiwanese Depression Questionnaire (TDQ) which were assessed pre-treatment and then after every five training sessions. Results Both groups demonstrated significant improvement pre- and post-treatment for the BBS (robotic group p = 0.023; control group p = 0.033) but no significant difference (p > 0.1) between the groups were found. However, the robotic training group had more participants demonstrating larger BBS points of improvement as well as greater Brunnstrom stage of improvement, when compared to the control group. No significant within and between group statistical differences (p > 0.3) were found for Pittsburgh Sleep Quality Index and Taiwanese Depression Questionnaire. Conclusion The addition of robotic gait training on top of standard hospital neurorehabilitation for acute stroke patients appear to produce a slightly greater improvement in clinical functional outcomes, which is not transferred to psychological status.

Characterization and expression pattern analysis of pheromone receptor-like genes in Winter Mushroom Flammulina filiformis - Li Meng; Tiansheng Chou; Siyuan Jiang; Li Wang; Mengjuan Zhu; Irum Mukhtar; Baogui Xie; Wei Wang (Archives of Microbiology, 2020)

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

The Rpf84 gene, encoding a ribosomal large subunit protein, RPL22, regulates symbiotic nodulation in Robinia pseudoacacia - Zhao Feng; Lu Zhang; Yuanyuan Wu; Li Wang; Mingying Xu; Mo Yang; Yajuan Li; Gehong Wei; Minxia Chou (Planta, 2019)

Anti-secretogranin III therapy of oxygen-induced retinopathy with optimal safety - Fen Tang; Michelle E. LeBlanc; Weiwen Wang; Dan Liang; Ping Chen; Tsung-Han Chou; Hong Tian; Wei Li (Angiogenesis, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Analysis of Electroencephalography Event-Related Desynchronisation and Synchronisation Induced by Lower-Limb Stepping Motor Imagery - Yi-Hung Liu; Li-Fong Lin; Chun-Wei Chou; Yun Chang; Yu-Tsung Hsiao; Wei-Chun Hsu (Journal of Medical and Biological Engineering, 2019)

Acetaminophen Poisoning May Increase Coronary Artery Disease Risk: A Nationwide Cohort Study - Yu-Ting Chung; Che-Yi Chou; Wen-Chen Tsai; Wei-Kung Chen; Cheng-Li Lin; Wei-Sheng Chung (Cardiovascular Toxicology, 2018)

Erratum to: Hypoxia Augments Increased HIF-1a and Reduced Survival Protein p-Akt in Gelsolin (GSN)-Dependent Cardiomyoblast Cell Apoptosis - Yu-Lan Yeh; Wei-Syun Hu; Wei-Jen Ting; Chia-Yao Shen; Hsi-Hsien Hsu; Li-Chin Chung; Chuan-Chou Tu; Sheng-Huang Chang; Cecilia-Hsuan Day; Yuhsin Tsai; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2018)

The status evaluation of the permafrost environment along the Chaida’er-Muli Railway in southern Qilian Mountains in northern Qinghai Province, China - Wei Cao; Yu Sheng; Ya-ling Chou; Ji-chun Wu; Jing Li; Sheng-ting Wang (Journal of Mountain Science, 2016)

Hypoxia Augments Increased HIF-1α and Reduced Survival Protein p-Akt in Gelsolin (GSN)-Dependent Cardiomyoblast Cell Apoptosis - Yu-Lan Yeh; Wei-Jen Ting; Chia-Yao Shen; Hsi-Hsien Hsu; Li-Chin Chung; Chuan-Chou Tu; Sheng-Huang Chang; Cecilia-Hsuan Day; Yuhsin Tsai; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2016)

A translationally controlled tumor protein gene Rpf41 is required for the nodulation of Robinia pseudoacacia - Minxia Chou; Congcong Xia; Zhao Feng; Yali Sun; Dehui Zhang; Mingzhe Zhang; Li Wang; Gehong Wei (Plant Molecular Biology, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Estimating the tendency of motor unit recruitment during steady-hold and rapid contractions using surface EMG and Turns-amplitude analysis - Li-Ling Pan; Chung-Huang Yu; Mei-Wun Tsai; Shun-Hwa Wei; Li-Wei Chou (European Journal of Applied Physiology, 2015)

Enhanced Therapeutic Epidermal Growth Factor Receptor (EGFR) Antibody Delivery via Pulsed Ultrasound with Targeting Microbubbles for Glioma Treatment - Ai-Ho Liao; Hsin-Yi Chou; Yi-Lei Hsieh; Sheng-Chieh Hsu; Kuo-Chen Wei; Hao-Li Liu (Journal of Medical and Biological Engineering, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Double homeobox gene, Duxbl, promotes myoblast proliferation and abolishes myoblast differentiation by blocking MyoD transactivation - Shey-Lin Wu; Guo-Zili Li; Chin-Yi Chou; Ming-Shiun Tsai; Yi-Pei Chen; Chung-Jung Li; Gan-Guang Liou; Wen-Wei Chang; Shen-Liang Chen; Sue-Hong Wang (Cell and Tissue Research, 2014)

Divergence of the expression and subcellular localization of CCR4-associated factor 1 (CAF1) deadenylase proteins in Oryza sativa - Wei-Lun Chou; Li-Fen Huang; Jhen-Cheng Fang; Ching-Hui Yeh; Chwan-Yang Hong; Shaw-Jye Wu; Chung-An Lu (Plant Molecular Biology, 2014)

Effect of caffeic acid on Ca2+ homeostasis and apoptosis in SCM1 human gastric cancer cells - Hong-Tai Chang; I-Li Chen; Chiang-Ting Chou; Wei-Zhe Liang; Daih-Huang Kuo; Pochuen Shieh; Chung-Ren Jan (Archives of Toxicology, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

The role of inferior frontal gyrus and inferior parietal lobule in semantic processing of Chinese characters - Tai-Li Chou; Chih-Wei Chen; Mei-Yao Wu; James R. Booth (Experimental Brain Research, 2009)

Membrane Tension Modulates the Effects of Apical Cholesterol on the Renal Epithelial Sodium Channel - Shi-Peng Wei; Xue-Qi Li; Chu-Fang Chou; You-You Liang; Ji-Bin Peng; David G. Warnock; He-Ping Ma (The Journal of Membrane Biology, 2007)

Independent [Ca2+]i increases and cell proliferation induced by the carcinogen safrole in human oral cancer cells - Jong-Khing Huang; Chun-Jen Huang; Wei-Chuan Chen; Shiuh-Inn Liu; Shu-Shong Hsu; Hong-Tai Chang; Li-Ling Tseng; Chiang-Ting Chou; Chih-Hung Chang; Chung-Ren Jan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Dual action of palmitoyl trifluoromethyl ketone (PACOCF 3 ) on Ca 2+ signaling: activation of extracellular Ca 2+ influx and alteration of ATP- and bradykinin-induced Ca 2+ responses in Madin Darby canine kidney cells - Chung-Ren Jan; Kang-Ju Chou; Kam Chung Lee; Jue-Long Wang; Li-Ling Tseng; Jin-Shiung Cheng; Wei-Chuan Chen (Archives of Toxicology, 2000)